Effect of solvents extraction on the antioxidant activity of Acacia polyacantha gum - Mohammedelnour, Ahmed A.; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Alam, Md. Zahangir; Abdullah, Amina; Musa, Khalid Hamid (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Acacia polyacantha gum (APG) is a dried exudate which obtained from the stems and branches of Acacia polyacantha trees, rich in soluble dietary fibers and organic compounds that appear to be capable of preventing many diseases. This study allowed for quantitation of the levels of total phenolic content (TPC) and antioxidant activity using ABTS and CUPRAC assays from APG extraction using pure solvents (methanol, ethanol, acetone) and their aqueous mixtures at 50% and 100%. The antioxidant levels were evaluated by 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS+) radical cation decolourisation and cupric iron reducing capacity in the presence of neocuproine (CUPRAC) for the evaluation of reducing power, and (TPC) was evaluated by the Folin-Ciocalteu method. As results, the solvent methanol (50%) gave the best extraction rates for APG presented by highest TPC (60.7833 ± 0.0416), CUPRAC (34.6533± 0.0611 mg TF/ 100g) and ABTS (34.6533± 0.0611 mg TF/ 100g) followed by ethanol 50%. On the other hand, pure methanol showed the lowest TPC (05.3300 ± 0.0608 mg GAE /100g DW), ABTS (10.9000 ± 0.0436 mg TF/ 100g), and CUPRAC (7.8000± 0.1249 mg TF/ 100g) values. Therefore, the variation in the antioxidant capacity between extracts was probably due to the differences in the nature of the APG compounds extracted using different solvents. The higher content of antioxidant activity in APG may have beneficial effects on the human health.